2020
DOI: 10.1038/s41420-020-0288-x
|View full text |Cite
|
Sign up to set email alerts
|

Protein-coated corrole nanoparticles for the treatment of prostate cancer cells

Abstract: Development of novel therapeutic strategies to eradicate malignant tumors is of paramount importance in cancer research. In a recent study, we have introduced a facile protocol for the preparation of corrole-protein nanoparticles (NPs). These NPs consist of a corrole-core coated with protein. We now report that a novel lipophilic corrole, (2)Ga, delivered as human serum albumin (HSA)-coated NPs, displayed antineoplastic activity towards human prostate cancer DU-145 cells. Cryo-TEM analysis of these NPs reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…The death cases in 2018 from 359,000 is projected to increase up to 740,000 cases in 2040, with a rise of new cases from 1,276,000 in 2018 to 2.3 million in 2040, because of increased numbers of the aging population (Culp et al, 2020). Depending on the levels of prostate-specific antigen and clinical stage of the patients, the treatment of patients with prostate cancer has opted for active surveillance, radiotherapy, or prostatectomy (Soll et al, 2020). Treatment option of prostate cancer includes androgen deprivation therapy as the mainstay management, however, the condition might progress to castration-resistant prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The death cases in 2018 from 359,000 is projected to increase up to 740,000 cases in 2040, with a rise of new cases from 1,276,000 in 2018 to 2.3 million in 2040, because of increased numbers of the aging population (Culp et al, 2020). Depending on the levels of prostate-specific antigen and clinical stage of the patients, the treatment of patients with prostate cancer has opted for active surveillance, radiotherapy, or prostatectomy (Soll et al, 2020). Treatment option of prostate cancer includes androgen deprivation therapy as the mainstay management, however, the condition might progress to castration-resistant prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…87). [235][236][237][238][239][240][241] Corrole conjugates have been the subject of a recent review from Sessler and coworker. 242 Main group corroles and their photophysical properties have been recently reviewed by Gross and Churchill.…”
Section: Photodynamic Therapy (Pdt) Applicationsmentioning
confidence: 99%
“…Fig.87Gallium A 3 -and trans-A 2 B-corrole complexes tested as potential photosensitizers in PDT [235][236][237][238][239][240][241]. …”
mentioning
confidence: 99%
“…[91] Recently, a lipophilic Ga(III) corrole delivered in as human serum albumin (HSA)-coated NPs (Ga/ HSA NPs), displayed antineoplastic activity towards human prostate cancer DU-145 cells. [82] These NPs were taken up via endocytosis and induced plasma membrane destabilization, impairment of calcium homeostasis, lysosomal stress and rupture, generation of reactive oxygen species (ROS), and consequently necrosis (Figure 5). These studies demonstrated the distinctive action of Ga(III) corroles and also provided abundant strategies to design and deliver Ga(III) compounds with enhancing drug concentration.…”
Section: Planar Tetradentate Ligandsmentioning
confidence: 99%